Determinants Influencing Elderly Utilization of Rumah Kasih: Social and Professional Support Analysis - Basyariah Lubis; Nur Indrawaty Lipoeto; Rozi Sastra Purna; Rosfita Rasyid (GLOBAL HEALTH SCIENCE GROUP, 2025)
Indonesia’s aging population presents an increasing demand for accessible, community-based health services. However, the utilization of Rumah Kasih, a community health program for older adults, remains suboptimal. Objective to examine the reinforcing factors influencing its utilization, including support from healthcare workers, university students, community health workers (CHWs), village heads, family members, and peers. A quantitative, cross-sectional study was conducted involving 192 elderly respondents with total sampling. Data were collected using questionnaires and analyzed using chi-square tests and multivariate logistic regression. The bivariate analysis indicated that all support factors were significantly associated with service utilization (p < 0.05). Multivariate analysis identified healthcare worker support as the most influential predictor (OR = 48.346; p < 0.001), followed by student involvement (OR = 5.259; p = 0.005). Although family support was significant in the bivariate analysis, it was not retained in the multivariate model. CHW and peer support yielded high odds ratios but lacked statistical significance, possibly due to data variability or multicollinearity. These findings highlight the critical role of professional engagement and student participation in enhancing elderly involvement in community health programs. Strengthening these factors, along with targeted strategies to involve social actors, may improve the effectiveness and long-term sustainability of elderly care services.